A comparison of the HIPERLAN - Doufexi, A.
At present, WLANs supporting broadband multimedia communication are being developed and standardized around the world. Standards include HIPERLAN/2, defined by ETSI BRAN, 802.11a, defined by the IEEE, and HiSWANa defined by MMAC. These systems provide channel adaptive data rates up to 54 Mb/s (in a 20 MHz channel spacing) in the 5 GHz radio band. An overview of the HIPERLAN/2 and 802.11a standards is presented together with software simulated physical layer performance results for each of the defined transmission modes. Furthermore, the differences between these two standards are highlighted (packet size, upper protocol layers etc.), and the effects of these differences on throughput are analyzed and discussed
Keywords: 20 MHz; 5 GHz; 54 Mbit/s.; ETSI BRAN; European Telecommunications Standards Institute; HIPERLAN/2 standards; HiSWANa; IEEE; IEEE 802.11a wireless LAN standards; MMAC; SHF; Broadband multimedia communication; Channel adaptive data rates; Channel models; Channel spacing; Medium access control; Packet size; Radio band; Software simulated physical layer; Performance results; Standardization; Throughput analysis; Transmission modes; Upper protocol layers